Diagnosis and management of rare paediatric Non-Hodgkin lymphoma. Issue 1 (March 2023) - Xavier, Ana C.; Suzuki, Ritsuro; Attarbaschi, Andishe
Abstract: Mature B-cell lymphomas, (B- or T-cell) lymphoblastic lymphomas (LBL), and anaplastic large cell lymphoma (ALCL) correspond to about 90% of all non-Hodgkin lymphoma (NHL) cases occurring in children and adolescents. The remaining 10% encompass a complex group of entities characterized by low/very low incidences, paucity of knowledge in terms of underlying biology in comparison to their adult counterparts, and consequent lack of standardization of care, information on clinical therapeutic efficacy and long-term survival. At the Seventh International Symposium on Childhood, Adolescent and Young Adult NHL, organized on October 20–23, 2022, in New York City, New York, US, we had the opportunity to discuss clinical, pathogenetic, diagnostic, and treatment aspects of certain subtypes of rare B- or T-cell NHL and they will be the topic of this review.